The effective hiring manager - Horstman, Mark (Wiley, 2020)
"Before one can become a truly effective manager to their teams, they need to create those teams. In many ways, finding the right person for the job AND integrating them into an existing team can be exponentially harder than managing that person/team. It's a problem faced by managers across all enterprises. Written by Mark Horstman, an expert in training managers, The Effective Hiring Manager will help managers across any and all organizations (from team leaders to HR professionals) by taking them step-by-step through ALL aspects of the hiring process; from posting a job to candidate selection, the interviewing process to integration with the team. Readers will learn what qualities to look for in a candidate, what questions to ask during an interview, what steps to take post-interview, etc."--
Includes index. - Description based on print version record; title from PDF title page, viewed (05/27/2020)
Keywords: Executive ability; Employees -- Recruiting; Supervision of employees; Management; Aptitude pour la direction; Personnel; Recrutement; Personnel; Supervision; Gestion; management; BUSINESS & ECONOMICS; Management; Employees; Recruiting; Business